Estrogen and Progesterone Receptor Expression in Epithelial Ovarian Cancers and Their Correlation with Histologic Subtypes, Grades and Immnuoexpression - Zahra, Kanwal; Khalid, Ahmareen; Tanwan, Ashok Kumar i (International Journal of Pathology, 2018)
Context: Ovarian cancer is the most fatal gynecological malignancy and its major burden is shared by EpithelialOvarian Cancers (EOC). Total 85% of all ovarian cancers belonged to EOC. Despite knowing the involvement ofEstrogen and Progesterone in their carcinogenesis, complete understanding of how they transform ovarian surfaceepithelium (OSE) is still unknown. Their associations with EOC may differ by different subtypes and grades which canbe helpful in determining the hormonal need of each. This knowledge can also be valuable for targeted hormonaltherapies comparable to those already established in carcinoma breast.Objective: To evaluate Estrogen and Progesterone receptor expression in various histologic subtypes and grades ofEpithelial Ovarian Cancers.